Anomalous Recognition of Sirri Marriage through the Status of 'Unrecorded Marriage' in Permendagri No. 108/2019 - waton rosyit, achmad nasrul (LPPM STAI Muhammadiyah Probolinggo, 2025)
The Ministry of Domestic Affairs Regulation No. 108 of 2019, which recognizes the status of